PREFERENSI MASYARAKAT TERHADAP TRANSPORTASI PUBLIKDI KOTA BANDA ACEH(Studi Kasus Bus Trans Koetaradja) - Henri Prianto Sinurat; Jul Fahmi Salim; Citra Permatasari (JURNAL EKOMBIS, 2020)
This  study  aims  to  look  at  the  factors  that  influence  the  preferences  of  the  people  of  Banda Aceh  in  using  the  Trans  Koetaradja  Bus.  The  data  used  are  primary  data  obtained  from distributing questionnaires electronically through Google forms, the number of respondents who filled Google Forms was 57 respondents. The results of the study show that the preferences of the people of Banda Aceh City are significantly influenced by the level of income, the higher th e level  of  opinion of a  person,  the  smaller  the  level  of use of  Trans Koetaradja  Buses, while  the travel  time  to  bus  stops  and  distance  does  not  significantly  influence  the  intensity  level  of  the use of Trans Koetaradja Bus in the city of Banda Aceh Keywords: Trans Koetardja, Income, Transportation